Beyond Balassa and Samuelson: Real convergence, capital flows, and competitiveness in Greece - Ansgar Belke; Ulrich Haskamp; Gunther Schnabl; Holger Zemanek (Research On Money in the Economy (ROME), 2015)
We scrutinize the role of capital flows in competitiveness in a set of seven euro-area member countries (Estonia, Greece, Latvia, Lithuania, Portugal, Slovenia, and the Slovak Republic) in the context of real convergence and crisis. A specific focus is on Greece. The paper extends the seminal Balassa-Samuelson model to include international capital markets, placing a particular focus on their impact on national wage policies. Capital flows are assumed to be able to invert the traditional direction of transmission of real wage increases from the tradable sector to the non-tradable sector and to cause real wages to increase beyond productivity increases. The augmented Balassa-Samuelson model is extended to trace cyclical deviations of real exchange rates from the productivity-driven equilibrium path. Panel estimations for the period from 1995 to 2013 show evidence of the Balassa-Samuelson effect if Greece is excluded from the panel. For Greece, this in turn provides evidence in favour of capital inflow-driven real wage increases in excess of productivity increases.
Keywords: E24; F16; F31; F32; 330; Balassa-Samuelson effect; capital inflows; exchange rate regime; inflation; Greece; Latvia; Portugal; panel model; productivity differential; wages